2019
DOI: 10.1038/s41467-019-12914-y
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the complete E. coli DNA gyrase nucleoprotein complex

Abstract: DNA gyrase is an essential enzyme involved in the homeostatic control of DNA supercoiling and the target of successful antibacterial compounds. Despite extensive studies, a detailed architecture of the full-length DNA gyrase from the model organism E. coli is still missing. Herein, we report the complete structure of the E. coli DNA gyrase nucleoprotein complex trapped by the antibiotic gepotidacin, using phase-plate single-particle cryo-electron microscopy. Our data unveil the structural and spatial organizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
147
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(161 citation statements)
references
References 65 publications
(95 reference statements)
11
147
3
Order By: Relevance
“…However, the hTop2α DNA binding/cleavage domain is still able to oscillate between the closed and pre-opening states in presence of etoposide, despite the fact that the G-segment base pairs remain annealed (see supplemental analysis). This conformational oscillation has also been observed in different bacterial DNA gyrase complexes bound to antibiotics 30,31 (Figure 3, Supplementary Fig. 3 and 8).…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…However, the hTop2α DNA binding/cleavage domain is still able to oscillate between the closed and pre-opening states in presence of etoposide, despite the fact that the G-segment base pairs remain annealed (see supplemental analysis). This conformational oscillation has also been observed in different bacterial DNA gyrase complexes bound to antibiotics 30,31 (Figure 3, Supplementary Fig. 3 and 8).…”
Section: Resultssupporting
confidence: 67%
“…The complete architecture of the hTop2α reveals the intertwined arrangement of the two subunits, a feature that was deduced from the yeast enzyme crystal structure and recently observed in the cryo-EM models of the prokaryotic Topo II 12,30 (Figure 2d and Figure 3d-f). The dimeric ATPase domain sits in a ~95°orthogonal orientation above the DNA-gate, similar to what was previously observed with the yeast Top2 (~90° orientation) 12 (Figure 3d-f).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Strikingly, most of the SUMO sites in the catalytic domains were identified along the dimeric interface of the Top2a structure [ Figure 3]. Structure determination of Top2 has shown that the subunits form an intertwined dimer structure and that the buried surface could be accessible during the catalytic cycle [ Figure 1B] [66][67][68][69] .…”
Section: Ubiquitinations and Sumoylationsmentioning
confidence: 99%